2015
DOI: 10.1007/s00170-015-7272-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid in molten pool on the welds with Ti-6Al-4V during pulsed arc welding

Abstract: Titanium alloy is one of the most popular materials in engineering applications. Pulsed arc welding can obtain grain refinement of titanium that is a benefit for mechanical properties. However, the study found that the optimized effect decreased with some higher frequencies. Hence, the study of Ti-6Al-4V was carried out with higher-frequency region, and the reason was discussed. The fluid of molten pool had effect on microstructure and mechanical properties of welding joints. Simultaneously, the arc behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One is that the arc pressure of the GTA can directly pushes the liquid metal towards the sidewalls [16], forming the favorable weld bead formation. The other reason is that the GTA inputs extra heat in the weld pool, which can enhance the fluidity of the liquid metal [17]. Figure 12 shows the microstructure when a GTA is added to the TW-GIA.…”
Section: Effect Of the Gta On Weld Bead Formationmentioning
confidence: 99%
“…One is that the arc pressure of the GTA can directly pushes the liquid metal towards the sidewalls [16], forming the favorable weld bead formation. The other reason is that the GTA inputs extra heat in the weld pool, which can enhance the fluidity of the liquid metal [17]. Figure 12 shows the microstructure when a GTA is added to the TW-GIA.…”
Section: Effect Of the Gta On Weld Bead Formationmentioning
confidence: 99%
“…Researchers have applied high frequency pulsed current to improve weldment microstructure and mechanical properties. Yang et al [16] studied the high-frequency pulsed arc welding of Ti-6Al-4V alloy at the frequency of 10-80 kHz, the elongation and fracture shrinkage were increased. Zhou et al [17] indicated that the low heat input of high frequency pulse welding was conducive to obtaining refined grain size, dense martensite αʹ organization and better tensile property.…”
Section: Introductionmentioning
confidence: 99%
“…Mingxuan Yang et al showed that the arc characteristics under pulsed current affect the molten pool fluid state which affects the microstructure and mechanical properties of welded joints. Additionally, the pulse frequency can optimize the mechanical properties of welded joints, such as toughness and ductility [23]. Wang, Y. J. et al showed that the high frequency pulse can produce an ultrasonic effect on arc and molten pool, and the amplitude of modulated pulse current is the main factor affecting ultrasonic sound pressure and power [24].…”
Section: Introductionmentioning
confidence: 99%